2018
DOI: 10.3390/ijerph15092039
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks Associated with Occupational Exposure to Ambient Air Pollution in Commercial Drivers: A Systematic Review

Abstract: Ambient air pollution is a major global health problem and commercial drivers are particularly exposed to it. As no systematic assessment of the health risks associated with occupational exposure to ambient air pollution in this population had yet been carried out, we conducted a systematic review using a protocol-driven strategy. Papers published from inception to April 20, 2018 in MEDLINE, EMBASE, CINAHL, African journals online, the Cochrane library, ISRCTN WHO ICTRP, and the Web of Science and Scopus datab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
8
0
3
Order By: Relevance
“…It was frequently confirmed that nurses worked more than 3-shift rotations for more than five consecutive days, working with less than 24-hours of rest between shifts, working with less than two nurses on night shifts, a backward rotation working system, etc. A previous study found that a backward rotation working system results in a worse work-life balance [24]. In October 2019, guidelines issued for night shifts for nursing staff proposed a night shift planning, including guaranteeing rest (48 hours and over) between consecutive two-night shifts, and limiting periods of consecutive night shifts to less than three days [25].…”
Section: Discussionmentioning
confidence: 99%
“…It was frequently confirmed that nurses worked more than 3-shift rotations for more than five consecutive days, working with less than 24-hours of rest between shifts, working with less than two nurses on night shifts, a backward rotation working system, etc. A previous study found that a backward rotation working system results in a worse work-life balance [24]. In October 2019, guidelines issued for night shifts for nursing staff proposed a night shift planning, including guaranteeing rest (48 hours and over) between consecutive two-night shifts, and limiting periods of consecutive night shifts to less than three days [25].…”
Section: Discussionmentioning
confidence: 99%
“…Current occupational epidemiological studies have been criticised for the use of imprecise proxies for diesel exposure, with occupational mortality often linked to years in job or against workers in non-exposed occupations (Fang et al 2010;Sun et al 2014). There have been reviews investigating the health effects of ambient pollution to commercial drivers (Lawin et al 2018), biomarkers of occupational exposure (Brucker et al 2020) and occupational exposures to diesel exhaust (Pronk et al 2009). However, none have identified studies investigating where and when the highest exposures for professional drivers occur and how these exposures could be mitigated.…”
Section: Professional Drivers and Occupational Exposure To Diesel Exhaustmentioning
confidence: 99%
“…Occupational exposure to air pollution is of particular concern where workers spend long periods close to emission sources, especially where air pollution regulations are not effectively implemented (Ngo et al, 2015;Fang et al, 2010). A systematic review of studies looking at occupational exposure of commercial bus drivers and motorcyclists to ambient air pollution found a signi cant difference in white blood cells amongst commercial motorcyclists, and an increased risk of lung cancer and Hodgkin's lymphoma amongst bus drivers, but found that the existing literature is limited (Lawin et al, 2018). In one of the few African studies, Ngo et al (2015) examined occupational exposure to roadside emissions in Nairobi, and found that bus drivers had signi cant exposure to black carbon (a component of PM 2.5 ) probably from vehicle smoke due to poor engine maintenance.…”
Section: Occupational Exposure To Air Pollutionmentioning
confidence: 99%